PROSPEK INDONESIA SEBAGAI MEDIATOR BAGI TERWUJUDNYA PERDAMAIAN ANTARA KOREA UTARA DAN KOREA SELATAN - Setia Ratna Dianpuri (HI 16 UMY 044, 2016)
*44 This paper aims to analyze Prospects of Indonesia as A Mediator for Peace Settlement between North Korea and South Korea. The conflict between North Korea and South Korea still in a ceasefire. Many parties have sought to resolve the conflict between the two Korea, but none of them found the best solution to resolve the conflict. Indonesia one of the country that concern about the conflict between North Korea and South Korea. In conflict resolution field Indonesia has experienced being a mediator for few conflict in ASEAN. Through these sources that support by role theory and peacemaking concept, the author found that Indonesia have a prospect for being a mediator, to resolve the conflict between North Korea and South Korea. Key Words: Role Theory, Peacemaking Concept, Resolution Conflict, Security Crisis, Susilo Bambang Yudhoyono regime